Influence of soft tissue thickness on marginal bone level around dental implants: A systematic review with meta‐analysis and trial‐sequential analysis - Bressan, Eriberto; Guazzo, Riccardo; Tomasi, Cristiano; Peña, Teresa Gutiérrez; Galindo‐Moreno, Pablo; Caponio, Vito Carlo Alberto; Sbricoli, Luca; Canullo, Luigi (Clinical oral implants research, 2023)
Objectives The aim of the present review and meta‐analysis was to evaluate the influence of soft tissue thickness on initial bone remodeling after implant installation. Materials and Methods A literature search was conducted by two independent reviewers on electronic databases up to May 2022. Randomized controlled trials (RCTs) and controlled clinical trials (CCTs) performed on human subjects were included. The risk of bias was evaluated using Cochrane Collaboration's tool. Meta‐analysis and Trial Sequential Analysis (TSA) were performed on the selected articles. The primary outcome was marginal bone loss. Results After screening, 6 studies were included in the final analysis, with a total of 354 implants, and a follow‐up from 10 to 14 months. 194 implants were placed in a ≥ 2 mm soft tissue thickness, while 160 had <2 mm soft tissue thickness before implant placement. The included studies had a high level of heterogeneity (I2 > 50%). The meta‐analysis indicated a statistically significant difference between the two groups (0.54; p = .027) and the TSA analysis confirmed the results, despite the limited number of dental implants. Additional analysis showed that age and follow‐up parameters were not statistically significant factors influencing the bone loss (p = .22 and p = .16, respectively). Conclusions Based on the available RCTS and CCTs, initial soft tissue thickness seems to influence marginal bone loss after a short follow‐up period. Based on TSA analysis, further studies are needed to assess the influence of the soft tissue thickness on marginal bone loss. PROSPERO registration number: CRD42021235324.